Oil and the duration of dictatorships - Jesus Crespo Cuaresma; Harald Oberhofer; Paul Raschky (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper studies empirically the relationship between oil endowment and the duration of autocratic leaders. A simple theoretical setting shows how the relationship between oil endowment and the duration of the dictatorial regime is mediated by the price of oil. Using a dataset on 106 dictators, our empirical analysis supports the predictions of the theoretical model and indicates that dictators in countries which are relatively better endowed in terms of oil stay longer in office. This result is robust to changes in the definition of dictatorial regimes, as well as to controlling for other economic and political variables.
Keywords: Q34; D72; H11; 330; Natural resources; dictatorship; political economy; duration